Trabajo en equipo: un reto para el aprendizaje basado en retos (Memorias Sifored - Encuentros Educación UAN, 2021)
The results of the study carried out with 85 first-year chemistry students at Universidad de La Sabana are presented, in which it was sought to identify the perception of students regarding the development of teamwork competence based on Challenge-Based Learning. Two validated instruments were used to collect the information that was evaluated with correlation tests and factor analysis. The results show that there is a strong correlation between decision-making, verbal communication, goal management, and conflict management, demonstrating the importance of dialogue and mediation to manage the project. Oral, verbal, and interpersonal communication was recognized as a highly developed and important competence to achieve goals. The variables were grouped into 3 components that explained the students' perception of teamwork. The teamwork competition was developed through strategy and the students recognized its importance.
Keywords: Competency education; teamwork; collaborative learning; challenge-based learning; chemistry